The Use of Peanut’s Shells and Sawdust Absorbents for Reduced Iron (Fe) Levels of Dug Well Water Puspitaloka Residence Housing at Tanjungpinang City in 2019 - Juliana Juliana; Hevi Horiza; Rinaldi Daswito (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2020)
Iron (Fe) levels in the dug well water of the community in Puspitaloka Residence Housing exceeded the quality standard so processing is needed to reduce the levels of iron contained in the dug well water. The purpose of this study was to determine the differences use of peanut's skin and sawdust absorbents to reduce levels of ferrous in dug well water. This study included pre-experimental research using the design of the one group pretest-posttest. The sampling technique was used in a purposive sampling method. Data analysis were Univariate and Bivariate analysis. Statistical tests used the Wilcoxon Signed Rank test and the Mann Whitney Test. The results showed a decrease in ferrous content using them. The presence of cellulose content in its had the potential to absorb iron. The results of the treatment the highest decrease, using peanut's shells absorbents occurred in the addition of 5 grams with a percentage of 54.41%. While the treatment using sawdust absorbent, occurred at the addition of 10 grams with a percentage of 84.43%. There was a difference the used of peanut's shells and sawdust absorbents to reduce iron levels in the water of the Puspitaloka Residence Housing dug well.